AN ANALYSIS OF DEIXIS IN “HOW TO TRAIN YOUR DRAGON 2” MOVIE SCRIPT - Asviea Suci Mukaromah (IKIP Siliwangi, 2022)
This research aimed to analyze the type of deixis in “How to Train Your Dragon” movie script by Dean DeBlois. This research method used descriptive qualitative. The collected data used movie script. Based on this research, the writer found that person deixis is the most dominant than the others. Person deixis used in this movie script is 789 times or 87.36%, consisting of the first person used 358 times or 39.64%, the second person 314 times or 34.77%, and the third person 117 times or 12.95%. The next spatial deixis was used 90 times or 9.96% and the last temporal deixis was used 24 times or 2.65%. Keywords: Pragmatics, Deixis, Movie Script